Identification and validation of neutrophil-related biomarkers in acute-on-chronic liver failure - Wei Lin; Yongping Chen; Yongping Chen; Mingqin Lu; Cheng Peng; Cheng Peng; Xiang Chen; Xiang Chen; Xiaoqin Liu; Yunyun Wang; Yunyun Wang (Frontiers in Immunology)
Dysfunction of peripheral blood neutrophils occurs in acute-on-chronic liver failure (ACLF). However, the molecular mechanisms of neutrophils involved in the pathophysiology of the ACLF remains poorly understood. Data downloaded from the GEO database (GSE142255) was used to identify both ACLF and neutrophil-related genes with the help of the limma package and Weighted Gene Co-Expression Network Analysis (WGCNA) algorithms. The analysis identified 288 ACLF-related differentially expressed genes (DEGs) in the circulating blood cells. Among these, three genes were found to be related to neutrophils and were identified as diagnostic genes, exhibiting high diagnostic efficacy as evidenced by an area under the curve (AUC) value of 1. Among these, matrix metallopeptidase-9 (MMP9) and S100 calcium binding protein A12 (S100A12) were upregulated, whereas C-C chemokine ligand 5 (CCL5) was downregulated in circulating immune cells from patients with ACLF compared to those from healthy controls. These findings were corroborated using an additional GEO dataset, GSE156382. The expression levels of the three key genes demonstrated a correlation with both ferroptosis and cuprotosis. Among the three diagnostic genes, only MMP9 was validated as differentially expressed through both quantitative real-time PCR (qRT-PCR) and western blot. Moreover, a significant elevation in plasma MMP9 levels was observed in patients with ACLF compared to those with chronic hepatitis B (CHB) and acute decompensated cirrhosis (AD). Notably, ACLF patients exhibiting elevated MMP9 levels (>175.8 ng/mL) experienced higher short-term mortality rates within both 30 and 90 days (p<0.001). In addition, a total of 21 drugs targeting the three diagnostic genes were identified from the Drug Bank database. Finally, the Kinase-TF-mRNA-miRNA network was constructed utilizing Cytoscape software. This study represents the initial application of WGCNA algorithms to identify novel biomarkers related to neutrophils in ACLF. Our findings offer new perspectives on the role of neutrophil in the pathogenesis of ACLF. However, additional research is required to substantiate the effects of these key genes and therapeutic agents on ACLF.